It's Ok to Fall. Issue 1 (1st June 2017) - Iohe, Taey
This piece of art writing imagines gravity and falling as quotidian experiences. There are two main characters: Muni (the name can be translated as Patterns, from the Korean original) and Garu (meaning Dust in Korean). Muni is undertaking a journey to a zero-gravity training facility in the small town of Shankill, Ireland; Garu works as a community-based psychologist. I chart her investigation of falling by taking a series of photographs and creating an installation. The installation is a room dusted with white powder, in which is hand-written a paragraph from a novel. This piece of art writing was exhibited as Language but No Words at the Space Mom Museum in Chungju, Korea in 2012.